MODEL WISATA RELIGI MASJID CHENG HOO PANDAAN SEBAGAI KATALISATOR ESKPLANASI NILAI- NILAI KEBUDAYAAN ISLAM DI PASURUAN - Dina Uswatun Hasanah; Ahmad Ma'ruf (Mu'allim, 2022)
The values of Islamic culture in supporting Pasuruan tourism contained in the Cheng Ho Pandaan mosque religious tourism model include three things, namely the first value of aqidah, which is contained in the elements of the Cheng Ho mosque building which is the emb odiment of Islamic symbols and is able to increase and foster belief in the oneness of Allah. swt. The two values of worship or ubudiyah are manifested through various Islamic activities such as marriage contracts, solemn prayer training, donations for o rphans, MTQ, banjari festivals, prayers, and regular recitations. While the third is the value of muamalah which is realized through buying and selling activities in the tourist market which has been running until now. For religious tourism, the Cheng Hoo Pandaan mosque has promoted in various ways, such as promotional strategies by the Pasuruan Regency government in collaboration with tourism ambassadors, promotional strategies through blogspot and tourists' social media, and are also often covered on tele vision shows and newspapers. However, this promotional activity is not only promoting the uniqueness of the mosque, but also through the activities carried out at the Cheng Hoo mosque. Through various activities that are supported by promotional media, thi s will invite many tourists to continue to come to this religious tourism. Both local and foreign tourists with different destinations.